Psychological momentum in football: the impact of a last-minute equalizer in a knock-out match - Den Hartigh, R. J. R.; Van Yarpen, N. W.; Gernigon, C. (Science and Medicine in Football, 2020)
What could be the impact of a last-minute equalizer on players' psychological momentum (PM) in a high-stake, knock-out football match? In the current study, 86 competitive male players were asked to imagine that they were playing in a cup final in which they were trailing 1-0 or leading 1-0. Subsequently, participants watched a video clip in which their team or the Opponent team scored the equalizer either in the 61st minute or 92nd minute (i.e., last-minute) of regulär playing time. Participants indicated their PM after the equalizer. Although the Situation became objectively neutral (1-1), results showed that PM was higher when players' own team scored than when the Opponent team did. More importantly, the equalizer had a particularly big impact on PM when the goal was scored last-minute. These results provide a better understanding of PM processes in football, and may explain the euphoria or despair of football players after a last-minute equalizer in a high-stake match.